ANALISIS TINGKAT KEPUASAN MAHASISWA TERHADAP LAYANAN PENDIDIKAN PADA FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS MATARAM - Junaidi Sagir; Alamsyah Abubakar; Emilia Septiani (Distribusi - Journal of Management and Business, 2021)
The purpose of this study is to measure satisfaction compared to performance on educational services for students of the Faculty of Economics and Business, University of Mataram, using the servqual model from Parasuraman et.al. which consists of fives dimensions, namely Tangible, Realibility, Responsiveness, Assurance and Emphaty. Respondents consisted of 135 students who were selected by purposive sampling from 3 majors which were evenly divided 45 students for each department. Data were analyzed using the Customer Satisfaction Index (CSI) and the Importance Performance Analysis (IPA).From the analysis it was found that: the average level of satisfaction in education services got a score of 15.5 with the IKM = 72.48% which was at the level of "Satisfactory" with service quality in the category of "Good". There is no wide gap between the level of satisfaction and the level of importance (expectation) in the three research majors.To increase student satisfaction, leaders need to pay attention to the dimensions that get the lowest satisfaction, such as the tangible dimension, which includes toilets, religious facilities, physical facilities, provision of a canteen, and other complementary facilities. Besides, it is necessary to increase the sensitivity of lecturers and staff to facilitate student affairs, especially in the thesis guidance process.